(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
A kidney transplant (KT) offers a significant survival benefit and is the only curative treatment for patients with ESRD. Infectious complications are still a leading cause of morbidity and death among transplant patients. This study aimed to assess the organisms and risk factors responsible for urinary tract and surgical site infection in allograft live-related renal transplant recipients during the early post-transplant period. This observational follow-up study was conducted among 20 purposively selected patients who underwent renal allograft transplant surgery from July 2019 to December 2020 in the Department of Urology, BSMMU, Dhaka. Patients with a history of renal transplant recipients or congenital renal anomalies and any urological malignancy were excluded from the study. After kidney transplant, UTI developed in 6 (30%) renal transplant recipients where all were complicated types and occurred between 10 to 14 days postoperatively. UTI was caused by E. coli in 3 (15%) patients, while Klebsiella and Enterococci were causative organisms for 1 (5%) and 2 (10.0%) patients, respectively. SSI developed in 3 (15%) renal transplant recipients where two were superficial, and one was deep. SSI occurred between 5-8 days postoperatively. SSI was caused by S. aureus in 2 (10%) patients and Pseudomonas in 1 (5%) patient. UTI was significantly more in older patients and the patients with a longer duration of catheterization. Older patients and overweight patients had significantly higher rates of SSI. In total, 33% of the recipient during the early hospital stay developed UTIs, all of which were complicated types. SSI developed in 15%, where 2/3rd was superficial and 1/3rd was deep. Older age with a longer duration of catheterization and DJ stent was found to be associated with the occurrence of UTI, while older age and high BMI were related to the event of SSI. BSMMU J 2022; 15(2): 127-131